Prevascularized hydrogels with mature vascular networks promote the regeneration of critical‐size calvarial bone defects in vivo. (5th February 2021) - Subbiah, Ramesh; Thrivikraman, Greeshma; Parthiban, S. Prakash; Jones, James M.; Athirasala, Avathamsa; Xie, Hua; Bertassoni, Luiz E.
Abstract: Adequate vascularization of scaffolds is a prerequisite for successful repair and regeneration of lost and damaged tissues. It has been suggested that the maturity of engineered vascular capillaries, which is largely determined by the presence of functional perivascular mural cells (or pericytes), plays a vital role in maintaining vessel integrity during tissue repair and regeneration. Here, we investigated the role of pericyte‐supported‐engineered capillaries in regenerating bone in a critical‐size rat calvarial defect model. Prior to implantation, human umbilical vein endothelial cells and human bone marrow stromal cells (hBMSCs) were cocultured in a collagen hydrogel to induce endothelial cell morphogenesis into microcapillaries and hBMSC differentiation into pericytes. Upon implantation into the calvarial bone defects (8 mm), the prevascularized hydrogels showed better bone formation than either untreated controls or defects treated with autologous bone grafts (positive control). Bone formation parameters such as bone volume, coverage area, and vascularity were significantly better in the prevascularized hydrogel group than in the autologous bone group. Our results demonstrate that tissue constructs engineered with pericyte‐supported vascular capillaries may approximate the regenerative capacity of autologous bone, despite the absence of osteoinductive or vasculogenic growth factors.